Language anxiety among university students: causal factors and coping strategies / Siti Faridah Kamaruddin - Kamaruddin, Siti Faridah (2015)
The purpose of this study was to investigate the level of English language anxiety among university students, the specific English language skills that causes the greater amount of language anxiety for university students, the possible factors that contribute to English language anxiety from the perspective of university students and the coping strategies to cope and alleviate English language anxiety from the perspective of highly anxious university students. This study employed a survey design with a mixed-method approach. A total of 125 Malaysian ESL university students from non English majors of different semesters participated in this study and completed two survey questionnaires for the data collection. A Demographic Background Questionnaire was used in order to obtain demographic information about the participants’ background. A self-developed questionnaire, the Factors of Language Anxiety Questionnaire (FLAQ) was used in order to assess the participants’ selfperceived anxiety levels, the specific skills that caused them greater anxiety and the main factors that contribute to their language anxiety in an English language classroom. Eight university students were chosen based on their high score on FLAQ to participate in eight standardized email interview sessions. The results of this study demonstrated that: (1) the majority of university students had a moderate level of selfperceived level of anxiety in an English language classroom; (2) writing skill is identified as the most anxiety-provoking skill among university students; (3) instructor-students interaction is considered as the main factor that contribute to language anxiety among university students; and (4) the highly anxious students employed the coping strategies such as utilizing language learning strategies, relaxation and preparation. The conduct of this study can provide pedagogical implications for the instructors in giving them the awareness of language anxiety and in creating an anxiety-reduced English language classroom.